2021
DOI: 10.3389/fnbeh.2020.598924
|View full text |Cite
|
Sign up to set email alerts
|

Destabilizing Different Strengths of Fear Memories Requires Different Degrees of Prediction Error During Retrieval

Abstract: Reactivation of consolidated memories can induce a labile period, in which these reactivated memories might be susceptible to change and need reconsolidation. Prediction error (PE) has been recognized as a necessary boundary condition for memory destabilization. Moreover, memory strength is also widely accepted as an essential boundary condition to destabilize fear memory. This study investigated whether different strengths of conditioned fear memories require different degrees of PE during memory reactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 60 publications
2
31
1
Order By: Relevance
“…Some of those studies have concluded explicitly that memory reactivation alone does not induce destabilization, e.g., [108,109]. Three of the most recent additions to that list [61,63,65] have for the first time tested the necessity of PE in the behavioral updating of human emotional memory, again confirming the PE requirement (as reviewed in Sections A. 14, A.16, and A.18).…”
Section: An Uphill Climb For the Prediction Error Requirementmentioning
confidence: 80%
See 4 more Smart Citations
“…Some of those studies have concluded explicitly that memory reactivation alone does not induce destabilization, e.g., [108,109]. Three of the most recent additions to that list [61,63,65] have for the first time tested the necessity of PE in the behavioral updating of human emotional memory, again confirming the PE requirement (as reviewed in Sections A. 14, A.16, and A.18).…”
Section: An Uphill Climb For the Prediction Error Requirementmentioning
confidence: 80%
“…These considerations also bear upon the findings of a sizable number of studies showing that reactivation mismatch has to be moderate, neither too mild nor too strong, in order to destabilize a memory, e.g., [22,59,65,[131][132][133][134][135][136][137]]. An inverted-U graph of destabilization probability versus degree of reactivation mismatch has been described [135].…”
Section: Sub-salient and Super-salient Mismatches Do Not Create A Pe Experiencementioning
confidence: 96%
See 3 more Smart Citations